PANDANGAN HUKUM EKONOMI SYARIAH TERHADAP PRAKTIK JUAL BELI MOBIL BEKAS MELALUI BROKER DI SHOWROOM SEDNA MOTOR KARTASURA - Lukmanul Hakim (Pusat Studi Ekonomi Islam Sekolah Tinggi Ekonomi Islam Hamfara, 2022)
This study analyzes the views of Islamic economic law on the practice of buying and selling used cars through brokers at the Sedna Motor Surakarta showroom. Researchers use the type of field research. This research use desciptive qualitative approach. The primary data source was taken by direct observation to the brokers. The researcher applied the snowball sampling technique. The secondary data sources in this study came from research journals and books. The data collection techniques used were used by researchers, namely interviews and documentation. The results of this study can be concluded that the practice of brokering at the Sedna Motor Kartasura Showroom according to the view of sharia economic law is permissible because the form of buying and selling that is practiced through a broker is carried out by upholding Islamic principles. used in the Sedna Motor Kartasura Showroom as a bridge connecting the transaction between the seller and the prospective buyer with the awareness that as a broker, it is the duty to bridge the transaction process, with honest and fair principles for both the seller and the prospective buyer. have good service quality, carry out marketing strategies and do not seek profits that harm both parties.